1999
DOI: 10.2337/diacare.22.5.795
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of postprandial versus interprandial blood glucose to HbA1c in type 1 diabetes on physiologic intensive therapy with lispro insulin at mealtime.

Abstract: The substitution of Hum-R with lispro (group 2) resulted in lower postprandial blood glucose, but greater postabsorptive blood glucose (P < 0.05 vs. group 1). The postprandial blood glucose AUC was lower (161 +/- 19 vs. 167 +/- 20 mg.100 ml-1.h-1), but the postabsorptive blood glucose AUC was greater (155 +/- 22 vs. 142 +/- 19 mg.100 ml-1.h-1) (P < 0.05). Therefore, the 24-h blood glucose AUC was no different (NS). Consequently, HbA1c was no different (NS). This occurred because in group 2, mealtime lispro res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
57
3
8

Year Published

1999
1999
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(69 citation statements)
references
References 1 publication
0
57
3
8
Order By: Relevance
“…Related to this observation we found that patients treated with sulfonylureas had greater post-prandial blood glucose excursions than subjects not taking these medications, suggesting that sulfonylureas are not able to prevent postprandial glucose peaks. Patients taking sulfonylureas who have poor glycaemic control thus might benefit from therapy with glinides and short-acting insulin analogues to control post-prandial hyperglycaemia [40][41][42][43][44][45][46].…”
Section: Discussionmentioning
confidence: 99%
“…Related to this observation we found that patients treated with sulfonylureas had greater post-prandial blood glucose excursions than subjects not taking these medications, suggesting that sulfonylureas are not able to prevent postprandial glucose peaks. Patients taking sulfonylureas who have poor glycaemic control thus might benefit from therapy with glinides and short-acting insulin analogues to control post-prandial hyperglycaemia [40][41][42][43][44][45][46].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have used multiple injection therapy [11,51, 54±57] or continuous subcutaneous insulin infusion (CSII) [41,42,58]. There has been a consistent improvement in HbA 1 c of 0.3±0.5 % points compared with the use of regular human insulin even when the latter was appropriately injected 30 min before meals (Table 1).…”
Section: Reviewmentioning
confidence: 91%
“…In one [57] out of six studies [11,51, 54±57] using similar treatment strategies of Type I diabetes mellitus, the hypoglycaemia rate has been lower during treatment with insulin lispro than with regular human insulin [39,61]. In a large study with over 1000 Type I diabetic patients and a statistical power high enough to detect changes in hypoglycaemia, the rate of hypoglycaemia was 12 % less during treatment with insulin lispro.…”
Section: Reviewmentioning
confidence: 99%
See 2 more Smart Citations